Management of Anticoagulation/Antiplatelet Medication and Venous Thromboembolism Prophylaxis in Elective Spine Surgery: Concise Clinical Recommendations Based on a Modified Delphi Process. Issue 5 (1st March 2023) - Zuckerman, Scott L.; Berven, Sigurd; Streiff, Michael B.; Kerolus, Mena; Buchanan, Ian A.; Ha, Alex; Bonfield, Christopher M.; Buchholz, Avery L.; Buchowski, Jacob M.; Burch, Shane; Devin, Clinton J.; Dimar, John R.; et al.
Abstract : Study Design: Delphi method. Objective: To gain consensus on the following questions: (1) When should anticoagulation/antiplatelet (AC/AP) medication be stopped before elective spine surgery?; (2) When should AC/AP medication be restarted after elective spine surgery?; (3) When, how, and in whom should venous thromboembolism (VTE) chemoprophylaxis be started after elective spinal surgery? Summary of Background Data: VTE can lead to significant morbidity after adult spine surgery, yet postoperative VTE prophylaxis practices vary considerably. The management of preoperative AC/AP medication is similarly heterogeneous. Materials and Methods: Delphi method of consensus development consisting of three rounds (January 26, 2021, to June 21, 2021). Results: Twenty-one spine surgeons were invited, and 20 surgeons completed all rounds of questioning. Consensus (>70% agreement) was achieved in 26/27 items. Group consensus stated that preoperative Direct Oral Anticoagulants should be stopped two days before surgery, warfarin stopped five days before surgery, and all remaining AC/AP medication and aspirin should be stopped seven days before surgery. For restarting AC/AP medication postoperatively, consensus was achieved for low-risk/medium-risk/high-risk patients in 5/5 risk factors (VTE history/cardiac/ambulation status/anterior approach/operation). The low/medium/high thresholds were POD7/POD5/POD2, respectively. For VTE chemoprophylaxis, consensus was achieved for low-risk/medium-risk/high-risk patients in 12/13 risk factors (age/BMI/VTE history/cardiac/cancer/hormone therapy/operation/anterior approach/staged separate days/staged same days/operative time/transfusion). The one area that did not gain consensus was same-day staged surgery. The low-threshold/medium-threshold/high-threshold ranges were postoperative day 5 (POD5) or none/POD3-4/POD1-2, respectively. Additional VTE chemoprophylaxis considerations that gained consensus were POD1 defined as the morning after surgery regardless of operating finishing time, enoxaparin as the medication of choice, and standardized, rather than weight-based, dose given once per day. Conclusions: In the first known Delphi study to address anticoagulation/antiplatelet recommendations for elective spine surgery (preoperatively and postoperatively); our Delphi consensus recommendations from 20 spine surgeons achieved consensus on 26/27 items. These results will potentially help standardize the management of preoperative AC/AP medication and VTE chemoprophylaxis after adult elective spine surgery.